2013
DOI: 10.1038/ng.2569
|View full text |Cite
|
Sign up to set email alerts
|

The draft genome of the fast-growing non-timber forest species moso bamboo (Phyllostachys heterocycla)

Abstract: l e t t e r sBamboo represents the only major lineage of grasses that is native to forests and is one of the most important nontimber forest products in the world. However, no species in the Bambusoideae subfamily has been sequenced. Here, we report a high-quality draft genome sequence of moso bamboo (P. heterocycla var. pubescens). The 2.05-Gb assembly covers 95% of the genomic region. Gene prediction modeling identified 31,987 genes, most of which are supported by cDNA and deep RNA sequencing data. Analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
474
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(518 citation statements)
references
References 57 publications
(52 reference statements)
27
474
2
1
Order By: Relevance
“…The reconstructed monocot nTNL phylogeny (Supplemental Fig. S1) revealed that nTNL genes from the six Poaceae species formed 456 monophyletic lineages, indicating the presence of at least 456 ancestral nTNL genes in the Poaceae common ancestor (;62 million years ago [MYA]; Peng et al, 2013. These Poaceae nTNL genes formed 57 monophyletic lineages when grouped with M. acuminata nTNL genes (one RNL lineage designated as Mo-R1, and 56 CNL lineages identified as Mo-C1 to Mo-C56), suggesting that nTNL genes from the seven monocot genomes were actually derived from 57 ancestral Mo-NBS genes ;110 MYA ( Fig.…”
Section: Phylogenetic Analysis Of Nbs Genes In Major Angiosperm Cladesmentioning
confidence: 99%
See 3 more Smart Citations
“…The reconstructed monocot nTNL phylogeny (Supplemental Fig. S1) revealed that nTNL genes from the six Poaceae species formed 456 monophyletic lineages, indicating the presence of at least 456 ancestral nTNL genes in the Poaceae common ancestor (;62 million years ago [MYA]; Peng et al, 2013. These Poaceae nTNL genes formed 57 monophyletic lineages when grouped with M. acuminata nTNL genes (one RNL lineage designated as Mo-R1, and 56 CNL lineages identified as Mo-C1 to Mo-C56), suggesting that nTNL genes from the seven monocot genomes were actually derived from 57 ancestral Mo-NBS genes ;110 MYA ( Fig.…”
Section: Phylogenetic Analysis Of Nbs Genes In Major Angiosperm Cladesmentioning
confidence: 99%
“…The Solanaceae nTNL genes formed 55 monophyletic lineages with nTNL genes from S. indicum (two RNL lineages The phylogenetic relationship was constructed according to the APG III system (Bremer et al, 2009). The divergence times at different nodes of angiosperms were combined from previous studies (Lavin et al, 2005;Stefanovic et al, 2009;D'Hont et al, 2012;Zhang et al, 2012;Peng et al, 2013;Yang et al, 2013;Kim et al, 2014;Wang et al, 2014;Zeng et al, 2014). The total number of NBS genes and their classification in each species are shown.…”
Section: Phylogenetic Analysis Of Nbs Genes In Major Angiosperm Cladesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many plants (Arabidopsis, Phyllostachys heterocycla, Mimulus guttatus, etc.) accelerate flowering to complete life cycle under drought conditions (Peng et al, 2013;Wolfe and Tonsor, 2014;Kooyers et al, 2015), a phenomenon referred to as drought escape (DE). Because drought triggers phytohormone abscisic acid (ABA) biosynthesis and signal transduction, it has been proposed that ABA mediates DE response.…”
mentioning
confidence: 99%